(untitled) (Research, Society and Development, 2020)
This work aims to analyze the environmental impacts of exploration and production of oil; to also discuss the potential of impacting activity for sensitive populations and ecosystems in the area of direct influence. Based on the understanding of the activities of the petroleum industry and refining processes, this is based on a literature search. Covers the main points of the story, the composition of the oil, extraction, production, geopolitics and development of oil activity. This article is to broaden the knowledge perspective on the impacts that the oil refining concerned for the environment, since several processes to obtain the final products of oil are needed for the derivatives are taken, these processes generate many damage natural resources especially water resources; also increasing the damage to the ecosystem.